Elite Capture Syndrome and Anti-Corruption Control in Nigeria: The Economic and Financial Crimes Commission and The Independent Corrupt Practices Commission in Perspective - Fisayo, Duyile Praise; Nte, Ngboawaji; Adejoke, Abdussalam Aishat; Ayoola, Olayiwola Richard (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2023)
Like many African states, Nigeria has hitherto been caught in the web of pervasive acts of grand and petty corruption. The pervasive nature of political and bureaucratic corruption in Nigeria has undeniably impoverished her economy and, as such, warranted the establishment of the EFCC and ICPC. However, anti-corruption agencies have not been able to control corruption to a minimum, as Nigeria remains poorly ranked in the global corruption index. This research takes on a critical and comparative lens to understand the nature of class politics in the fight against corruption, to examine the level of high-profile prosecutions, to identify irregularities in the institutions of law enforcement, and to consider the level of transparency and accountability for recovered loot and confiscated properties. The study finds, among other things, that powerful elites have high-jacked anti-corruption fights of the EFCC and ICPC, with low-profile convictions in Nigeria, and public accountability and transparency regarding recovered loot is almost nonexistent. The Elite Capture paradigm is employed as a theoretical guide in its narrative.